The A SURVEY OF PHARMACISTS’ KNOWLEDGE AND PRACTICE OF PHARMACOLOGICAL CARE IN INDIA - Devinder Kumar, Naveen Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In order to improve the patient's quality of life and assure the safety of pharmacotherapy, pharmaceutical care (PC) is an important part of healthcare. As a part of the multidisciplinary team caring for patients, a pharmacist should be included and pharmaceutical services should be integrated with medical care and nursing. This is a major problem for the Polish health care system.To assess the attitudes and knowledge of pharmacists in India towards the practise of PC and to identify the hurdles to the supply of PC.Methods: Polish pharmacists were recruited to participate in a multicentre trial. Using a random sample method, the study group was chosen at random. After gaining the pharmacists' verbal agreement to participate in the study, a face-to-face questionnaire approach was utilised to interview them. Research took place between January 2017 and September 2019, according to the results.As a result, just 15% of pharmacists have ever taken a PC training course. Pharmacotherapy safety was deemed essential by 72% of respondents. Only 63% of pharmacists feel that they are responsible for preventing and resolving health-related and drug-related issues for their patients. The lack of time, lack of legal rules, and lack of organisational facilities were the primary reasons for pharmacists not providing PC.As a result of this investigation, it can be concluded that India will soon deploy personal computers. There is an urgent demand for educational programmes in this area. Pharmacists should be required to have access to personal computers in their classrooms.